2015
DOI: 10.1111/ajt.13300
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of HLA-Specific Allosensitization From a Highly Sensitized Deceased Organ Donor to the Recipients of Each Kidney

Abstract: We report for the first time the adoptive transfer of donor HLA‐specific allosensitization in two recipients following kidney transplantation from a highly sensitized donor. Kidneys from a donation after circulatory death donor were transplanted into two nontransfused, HLA‐specific antibody negative males receiving their first transplant. Antibody screening 7 days after transplant showed high level de novo IgG HLA class I‐ and class II‐specific antibodies in both recipients, with largely overlapping antibody p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Several case reports describe a similar situation and timeline, and combined together offer a potential insight regarding the immune cell type responsible . Maxfield et al described 2 nonsensitized renal transplant recipients who developed third‐party anti‐HLA antibodies at 7 days that matched the sensitized donor profile and lasted beyond 3 months . B cells or plasma cells were considered the likely culprits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports describe a similar situation and timeline, and combined together offer a potential insight regarding the immune cell type responsible . Maxfield et al described 2 nonsensitized renal transplant recipients who developed third‐party anti‐HLA antibodies at 7 days that matched the sensitized donor profile and lasted beyond 3 months . B cells or plasma cells were considered the likely culprits.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our own report, these various case series suggest that donor lymphoid tissue originating memory cells (likely plasma cells) enter and remain in the recipient circulation long term. The case report utilizing rituximab, with no circulating B cells and the 2 case reports observing antibodies within a short 7 days from transplant, argue against the theory that B cells are the bridging cell that subsequently differentiates into plasma cells . Additionally, tissue‐resident B cells are associated with local antigens, so they should not be outside the allograft in significant numbers.…”
Section: Discussionmentioning
confidence: 99%
“…First, due to clonal expansion upon encounter with antigen, the memory pool is much larger than the naive T-cell pool for any given antigen. 62 Since de Leur et al have observed infiltration of host memory T cells into the graft tissue and differentiation into T rm , understanding the impact of lymphodepletion on alloreactive tissue resident memory cells is likely of clinical relevance. However, donor-derived T rm involvement in the failure to achieve long-term tolerance seems less likely according to their study since in host T rm cells dominate in grafts that reject beyond the first year.…”
Section: Metabolic Changes In Memory T Cells Confer More Rapid Recamentioning
confidence: 99%
“…However, it has been observed clinically that if a donor is highly sensitized to the recipient, allospecific responses can be generated post-transplant despite a lack of pre-existing donor-specific antibodies in the recipient during screening. 62 Since de Leur et al have observed infiltration of host memory T cells into the graft tissue and differentiation into T rm , understanding the impact of lymphodepletion on alloreactive tissue resident memory cells is likely of clinical relevance. Because homeostatic proliferation following lymphodepletion gives rise to T cells with a memory phenotype, it is possible that patients receiving lymphodepletion could develop T rm cells at increased frequencies relative to patients who do not undergo lymphodepletion prior to transplant.…”
Section: Increased Presence Of Tissue Resident Memory Cells Can Impmentioning
confidence: 99%
“…Other studies have documented post‐transplant HLA seroconversion in 50–76% of previously transplanted patients . In a single report, HLA‐specific allosensitization was thought to be transferred to the recipient from a highly sensitized organ donor . In individuals without a history of transplantation, depending on whether or not leukoreduced products are used, transfusion can account for 20 to 33% of sensitizing events .…”
Section: Hla System An Immunologic Barrier To Transplantationmentioning
confidence: 99%